Chapter Il Piccolo Masaccio e le Terre Nuove. Creativity and Computer Graphics for Museum Edutainment - Zucchi, Valentina (Proceedings e report, 2018)
Since its opening, the Museum of the New Towns, housed in the Palazzo di Arnolfo in San Giovanni Valdarno, has dedicated a particular attention to the relationship with its audiences. In this context, the video "Il piccolo Masaccio e le Terre Nuove" has the purpose of bringing children and young people, in particular, closer to the museum main themes. The video presents a series of very different techniques, such as live shots, taken also by drone, Computer Graphics, 2D drawings executed with a tablet, drawings sketched with traditional techniques, such as India ink and watercolours, and digital videos taken from Google Earth.